2024
DOI: 10.9734/jemt/2024/v30i61211
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Role of Trade on the Relationship between Environmental Quality and Energy Consumption: Insights from Sub Saharan Africa

Olugbenga Olaposi, Olaoye,
Faruq Umar Quadri,
Oluwaseun Oladeji Olaniyi

Abstract: This study looks at the relationship between energy consumption and environmental quality in Sub-Saharan Africa (SSA) and how trade with other countries affects it. It examines data from 35 SSA economies between 1996 and 2020, categorized into low-income (LICs) and middle-income (MIC) countries. Using the cross-sectional augmented autoregressive distributed lag (CS-ARDL) approach, the results show that energy use, especially in MICs, negatively affects environmental quality. Trade, however, considerably lessen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…The data shows a positive correlation between AI and automation adoption in sectors like education, healthcare, and agriculture, and improvements in related developmental indicators like literacy rates, healthcare access, and agricultural productivity [54,7,17]. This supports the theoretical proposition that technology can be a great equalizer, provided that foundational challenges such as infrastructure and education are addressed [55].…”
Section: Synthesis Of Research Findings and Theoretical Frameworksupporting
confidence: 55%
“…The data shows a positive correlation between AI and automation adoption in sectors like education, healthcare, and agriculture, and improvements in related developmental indicators like literacy rates, healthcare access, and agricultural productivity [54,7,17]. This supports the theoretical proposition that technology can be a great equalizer, provided that foundational challenges such as infrastructure and education are addressed [55].…”
Section: Synthesis Of Research Findings and Theoretical Frameworksupporting
confidence: 55%
“…Oil spillage has environmental and socioeconomic impacts in petroleum-producing areas, such as Nigeria's riverine regions [16]. Hjeldnes et al [17] found that oil spreads similarly in soil and along container walls, with movement slowing after seven days.…”
Section: Soil-oil Interactionmentioning
confidence: 99%
“…Additionally, the EU has proposed the Artificial Intelligence Act, which seeks to classify AI systems based on their risk levels and implement corresponding regulatory measures. This act aims to ensure that AI systems are safe, transparent, and respect fundamental rights [31,32].…”
Section: Existing Global Policies and Strategies On Ai Misusementioning
confidence: 99%